New resources inform study of genome size, content, and organization in nonavian reptiles - Janes, Daniel E. (Integr Comp Biol, 2008)
Genomic resources for studies of nonavian reptiles have recently improved and will reach a new level of access once the genomes of the painted turtle (Chrysemys picta) and the green anole (Anolis carolinensis) have been published. Eleven speakers gathered for a symposium on reptilian genomics and evolutionary genetics at the 2008 meeting of the Society for Integrative and Comparative Biology in San Antonio, Texas. Presentations described results of reptilian genetic studies concerning molecular evolution, chromosomal evolution, genomic architecture, population dynamics, endocrinology and endocrine disruption, and the evolution of developmental mechanisms. The presented studies took advantage of the recent generation of genetic and genomic tools and resources. Novel findings demonstrated the positive impact made by the improved availability of resources like genome annotations and bacterial artificial chromosomes (BACs). The symposium was timely and important because it provided a vehicle for the dissemination of novel findings that advance the field. Moreover, this meeting fostered the synergistic interaction of the participants as a group, which is anticipated to encourage the funding and creation of further resources such as additional BAC libraries and genomic projects. Novel data have already been collected and studies like those presented in this symposium promise to shape and improve our understanding of overall amniote evolution. Additional reptilian taxa such as the American alligator (Alligator mississippiensis), tuatara (Sphenodon punctatus), and garter snake (Thamnophis sirtalis) should be the foci of future genomic projects. We hope that the following articles in this volume will help promote these efforts by describing the conclusions and the potential that the improvement of genomic resources for nonavian reptiles can continue having in this important area of integrative and comparative biology.